2020
DOI: 10.1186/s40168-020-00816-x
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota from persons with attention-deficit/hyperactivity disorder affects the brain in mice

Abstract: Background: The impact of the gut microbiota on host physiology and behavior has been relatively well established. Whether changes in microbial composition affect brain structure and function is largely elusive, however. This is important as altered brain structure and function have been implicated in various neurodevelopmental disorders, like attention-deficit/hyperactivity disorder (ADHD). We hypothesized that gut microbiota of persons with and without ADHD, when transplanted into mice, would differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 81 publications
0
67
0
Order By: Relevance
“…This suggests that, even in the absence of significant correlations with other bacteria ( Figure S7), there could be a bacterial community interaction pattern that explains more variance than a genus alone on inattention symptoms. Lastly, our lab recently performed a separate study, in which six randomly selected samples from the NeuroIMAGE cohort (same cohort studied here) were used in an animal study of human fecal microbiota transplantation into germ-free wild-type mice [51]. Mice colonized with ADHD gut microbiota had increased anxiety-like behavior and showed significantly altered structural and functional brain characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, even in the absence of significant correlations with other bacteria ( Figure S7), there could be a bacterial community interaction pattern that explains more variance than a genus alone on inattention symptoms. Lastly, our lab recently performed a separate study, in which six randomly selected samples from the NeuroIMAGE cohort (same cohort studied here) were used in an animal study of human fecal microbiota transplantation into germ-free wild-type mice [51]. Mice colonized with ADHD gut microbiota had increased anxiety-like behavior and showed significantly altered structural and functional brain characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of a positive correlation of Prevotella with DMN and ECN functioning and also fronto-parietal attention network modulations support these results. Previous work showed a link between gut microbiota and restingstate functional connectivity, as assessed here (9,49). Interestingly, in one study assessing bivariate relationships, Prevotella and Bacteroides were associated with insular connectivity (8).…”
Section: Discussionmentioning
confidence: 77%
“…Recently, there are some efforts to control neurological disorders by applying the gut-brain axis theory, a bidirectional communication between the brain and gastrointestinal tract [ 50 , 51 ]. In cases of ADHD, there is evidence demonstrating that gut microbiota affects brain neurodevelopment [ 52 , 53 , 54 , 55 ]. For instance, Szopinska-Tokov et al suggested that inattentive behavior that appeared in ADHD patients is associated with a specific bacterium [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Szopinska-Tokov et al suggested that inattentive behavior that appeared in ADHD patients is associated with a specific bacterium [ 53 ]. Also, it is reported that colonizing microbiota from ADHD patients to experimental mice affects the alteration of brain structures and causes concomitant changes in the behavior [ 55 ]. In this study, we investigated intestinal perturbation in a PAE-induced ADHD-like mouse model and the regulatory effects of HX106 on the gut microenvironment by analyzing metabolite changes in colon and fecal samples.…”
Section: Discussionmentioning
confidence: 99%